Biopolymers Online 2001
DOI: 10.1002/3527600035.bpol1009
|View full text |Cite
|
Sign up to set email alerts
|

Soil Humic Substances

Abstract: Introduction Genesis The Lignin‐Protein Theory The Sugar‐Amine Theory The Polyphenol Theory Extraction, Fractionation and Purification Extraction Methods Fractionation Procedures Purification Procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 72 publications
0
23
0
7
Order By: Relevance
“…Results obtained by IR spectra have shown that carboxyl groups are the most important functional groups in HS, accounting for the majority of their charge, acidity, and metal and particle surface binding characteristics (Senesi and Loffedro, 2001;Stevenson, 1994). In HA spectra the carboxylate bands appear at 1624-1633 cm -1 and 1385-1383 cm -1 , respectively, depending on pH.…”
Section: Humic Substances Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Results obtained by IR spectra have shown that carboxyl groups are the most important functional groups in HS, accounting for the majority of their charge, acidity, and metal and particle surface binding characteristics (Senesi and Loffedro, 2001;Stevenson, 1994). In HA spectra the carboxylate bands appear at 1624-1633 cm -1 and 1385-1383 cm -1 , respectively, depending on pH.…”
Section: Humic Substances Characterizationmentioning
confidence: 99%
“…R-COOH and R-OH (Lumsdon and Fraser, 2005). On a mass basis, HA is less charged than FA, but HA shows more poliaromatic structure (Lumsdon and Fraser, 2005;Senesi and Loffedro, 2001). Some studies applied the FTIR spectroscopy to characterize functional groups (D'Orazio and Senesi, 2009;Francioso, et al, 2002) and biological properties of different HA molecular weight fractions.…”
Section: Humic Substances Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Humic compounds are produced primarily by abiotic reactions of relatively small molecules, such as lignins, lipids, and carbohydrates from plant and microbial biopolymers involving direct conversion; these abiotic reactions are then followed by degradation. 2 The Ariake Sea, which is a typical semi-closed bay located at Kyushu Island in Japan, has a maximum tidal range of about 6 m during the spring tide, and has a vast tideland area covered with several living organisms that are unique in Japan. 3 The unique living systems of this area are likely to be influenced by the circulation of organic and biological compounds from a combination of marine algae and other marine microorganisms that are produced and metabolized.…”
mentioning
confidence: 99%
“…Loffredo et al (2005) found that the allelopathic effects of SA, FA and CA on the early growth of tomato and lettuce disappeared with the addition of different humic or fulvic acids in their growing medium. HA fractions may interact with such monomeric compounds and act as a reaction partner and/or as a protecting ligand (Senesi and Loffredo 2001). The different responses of the fungus to the different allelopathic agents could be attributed to fungal enzymatic adaptation to the various available C sources (Souto et al 2000).…”
Section: Effects Of the Combinations Of Ha-allelochemicalmentioning
confidence: 99%